2014
DOI: 10.1007/s12032-014-0428-3
|View full text |Cite
|
Sign up to set email alerts
|

The downregulation of miR-200c/141 promotes ZEB1/2 expression and gastric cancer progression

Abstract: Gastric cancer is the fourth most common malignancy in the world. Although microRNA-200 (miR-200) family members are thought to play roles in tumorigenesis, their functions in carcinogenesis are tumor specific, and the underlying mechanism of action still remains elusive. Few studies to date have addressed the dysregulation and function of miR-200 family members in gastric cancer progression. Here, we report that the miR-200 family members, miR-200c and miR-141, were significantly downregulated in gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 45 publications
4
58
0
1
Order By: Relevance
“…Overexpression of miR-141 suppressed tumor growth and pulmonary metastasis in nude mice. In clinical samples, the expression of miR-141 was inversely correlated with TNM stage, tumor invasion depth, tumor embolus and disease-free survival [40]. Further study indicated that the miR-200c and miR-141 cluster (miR-200c/141) could inhibit migration and invasion of gastric cancer by directly targeting of ZEB1 and ZEB2 and the subsequent restoration of E-cadherin [100].…”
Section: Mir-141 and Tumor Invasion And Metastasismentioning
confidence: 95%
See 1 more Smart Citation
“…Overexpression of miR-141 suppressed tumor growth and pulmonary metastasis in nude mice. In clinical samples, the expression of miR-141 was inversely correlated with TNM stage, tumor invasion depth, tumor embolus and disease-free survival [40]. Further study indicated that the miR-200c and miR-141 cluster (miR-200c/141) could inhibit migration and invasion of gastric cancer by directly targeting of ZEB1 and ZEB2 and the subsequent restoration of E-cadherin [100].…”
Section: Mir-141 and Tumor Invasion And Metastasismentioning
confidence: 95%
“…Furthermore, DNA methylation maintains the balance of tissue-specific expression of the miR-200c/141 cluster in normal cells and affects the phenotypic changes observed in cancer cells. Current findings indicate that downregulation of miR-200c and miR-141 is due to a highly methylated CpG island located upstream of their genomic sequence and/or upregulated transforming growth factor (TGF)-β signaling [40]. The double-negative feedback loop controlling ZEB1 is perhaps the best known mechanism of miR-200c/141 action.…”
Section: Upstream and Downstream Pathways Of Mir-141mentioning
confidence: 99%
“…Deregulation of miR-200c has been identified to be associated with various types of human cancer, including ovarian, breast, prostate, gastric and bladder cancer (10)(11)(12)(13)(14). miR-200c has been identified as being frequently downregulated in ccRCC (15).…”
Section: Introductionmentioning
confidence: 99%
“…Using deep-sequencing analysis, we found that miR-141-3p expression was decreased by 1.26-fold in early PCa compared to that in BPH (P < 0.05), and confirmed a similar 1.17-fold decrease in early PCa compared to that in BPH (P = 0.2053) by qRT-PCR. In addition, miR-141-3p expression levels vary in different tumors, with overexpression observed in bladder [16], urothelial [17], breast [18] [19], ovarian [20], endometrioid [21], cholangiocytes [22] and colorectal cancers [23] and NSCLC [24], while expression is downregulated in gastric cancer [25], hepatocellular carcinomas [26] [27], renal cell carcinoma [28], lymphatic metastatic pancreatic cancer [29], pituitary tumors [30], craniopharyngioma [31], head and neck cancer [32], osteosarcoma [33], and cutaneous T cell lymphoma [34]. These reports provide compelling evidence for a role of miR-141-3p as an oncogene or tumor suppressor in different tumors and at different stages.…”
Section: Discussionmentioning
confidence: 99%